2020
DOI: 10.1038/s41598-020-70981-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HIV infection, antiretroviral therapy, and immune status on the speed of information processing and complex motor functions in adult Cameroonians

Abstract: HIV-associated neurocognitive deficits include impaired speed-of-information processing (SIP) and motor functions. There is lack of Cameroonian adult norms for assessing SIP or motor functions. This study of 683 Cameroonians (320 HIV+, 363 HIV−) establishes demographically-adjusted norms for six SIP [Wechsler-Adult-Intelligence-Scale (WAIS)-III Digit Symbol (WAIS-IIIDS) and Symbol Search (WAIS-IIISS), Stroop Color-Naming, Stroop Word-Reading, Trail-Making Test-A (TMT-A), Color Trails-1 (CTT1)], and two motor f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 98 publications
(125 reference statements)
0
5
0
Order By: Relevance
“…In these outbreaks, cognitive deficits were also centered on attention, executive functions, and memory. Furthermore, cognitive dysfunction in patients with a viral infection such as Human Immunodeficiency Virus (HIV) has also been reported in prior studies, in which deficits in attention, learning, and memory functions were reported 43 . Additionally, the Zika virus has also been reported to leave long-term cognitive sequelae 44 .…”
Section: Discussionmentioning
confidence: 67%
“…In these outbreaks, cognitive deficits were also centered on attention, executive functions, and memory. Furthermore, cognitive dysfunction in patients with a viral infection such as Human Immunodeficiency Virus (HIV) has also been reported in prior studies, in which deficits in attention, learning, and memory functions were reported 43 . Additionally, the Zika virus has also been reported to leave long-term cognitive sequelae 44 .…”
Section: Discussionmentioning
confidence: 67%
“…For the first time, our results underlined that the indirect effects of COVID-19, converging in PTSD symptomatology, affected executive functions. As reported regarding previous viral infections (e.g., H1N1, [ 29 ]; HIV, [ 30 , 31 ], and according to the results regarding the effect of the SARS-CoV-2 pandemic (for a review: [ 32 ]), cognitive impairment was recorded in infected patients, highlighting the role of the inflammatory processes as possible markers of these alterations [ 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…95 Substantial evidence abounds demonstrating HIV as a cause of neurocognitive disorders with about two-thirds of people living with HIV diagnosed with probable HIV-associated neurocognitive disorder (HAND). [96][97][98][99][100][101][102] With more than 11.3 million human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) patients affected by HAND, 98 it has been suggested that the burden of HAND in Africa is likely to rank among the highest of any region in the world. There are several reasons for the high burden of HAND on the continent.…”
Section: Modifiable Risksmentioning
confidence: 99%
“…Examples of normative data have been reported from Cameroon in the pediatric and adult populations. 99,153 For functional assessment, the Clinician Home-based Interview to assess Function (CHIF) was developed and validated by the Indianapolis-Ibadan dementia research group. 154 The IDEA study Instrumental Activities of Daily Living (IDEA-IADL) was also recently developed and validated among rural-dwelling Tanzanians.…”
Section: Cognitive Evaluation In Africamentioning
confidence: 99%
See 1 more Smart Citation